Simulations of Heat Transport Phenomena in a Three-Dimensional Model of Knitted Fabric - Puszkarz A.K. (Autex Research Journal, 2016)
The main goal of the current work is to analyse the three-dimensional approach for modelling knitted fabric structures for future analysis of physical properties and thermal phenomena. The introduced model assumes some simplification of morphology. First, fibres in knitted fabrics are described as monofilaments characterized by isotropic thermal properties. The current form of the considered knitted fabric is determined by morphological properties of the used monofilament and simplification of the stitch shape. This simplification was based on a particular technology for the knitting process that introduces both geometric parameters and physical material properties. Detailed descriptions of heat transfer phenomena can also be considered. A sensitivity analysis of the temperature field with respect to selected structural parameters was also performed.